Research on the evolution law of the seismic wave field based on the explosive source parameters - Yu, Chenglong; Shi, Xunxian; Gao, Quan; Zhang, Xingkai; Wang, Fengnian (Frontiers in Earth Science, 2023)
We present a numerical model for blast-induced seismic waves. This model is based on the transformation mechanism of seismic wave field, and the process of the seismic wave’s generation is divided as two stages. First stage is the generation of elastic waves. Due to the plastic deformation of the geotechnical medium in this stage, we have established the Euler model to describe it. Second stage is the prorogation of the elastic waves, we have established the LaGrange models to describe this stage. Finally, the influence of the main parameters of the explosive source (detonation pressure and expansion index) on the seismic wave is analyzed by the established model. The results show that the proposed model in this paper can reasonably predict the evolution law of seismic wave field based on the explosive source parameters.